2022
DOI: 10.1002/jee.20485
|View full text |Cite
|
Sign up to set email alerts
|

The climate is changing. Engineering education needs to change as well

Abstract: As atmospheric greenhouse gas concentrations continue to rise and the consequences of climate change become increasingly destructive, engineers, scientists, and the broader population are now aware that climate change is a threat we can no longer avoid. Addressing climate change requires facing two interconnected challenges. The first is to rapidly transition to carbon neutral-or even carbon negative-energy systems while reducing greenhouse gas emissions across all sectors of the economy. The second challenge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Furthermore, Holly commented on the importance of having administrative support for her teaching of science and engineering. Previous studies have reported that lack of administrative support is a barrier to the implementation of engineering in primary school classrooms [40,41]. Because Holly felt supported by her administrator, she was able to take the risk of incorporating new pedagogical strategies and content in her classroom-something she would not have been as inclined to do had she not had that support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Holly commented on the importance of having administrative support for her teaching of science and engineering. Previous studies have reported that lack of administrative support is a barrier to the implementation of engineering in primary school classrooms [40,41]. Because Holly felt supported by her administrator, she was able to take the risk of incorporating new pedagogical strategies and content in her classroom-something she would not have been as inclined to do had she not had that support.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the teachers in Radloff et al's study [38], Holly found that by implementing engineering-design-based teaching, levels of student engagement increased. Furthermore, community-focused engineering education (e.g., flood mitigation) can also help students understand how climate and sustainability are connected to engineering design [41], connecting to multiple principles of the Engineering for Sustainable Communities framework [19].…”
Section: Discussionmentioning
confidence: 99%
“…[30] Martin et al asserted how engineering education must be adaptive in this environment of uncertainty and rapid change. [31] In particular, they focus on the need to link engineering design with climate and sustainability contexts, incorporate various disciplines into engineering solutions, consider justice and ethics dimensions, and collaborate with diverse communities. Other approaches, such as engineering leadership, [11,32,33] engineering design, [34,35] and emerging learning environments, [36] offer integrated forms of education.…”
Section: Contextmentioning
confidence: 99%
“…Furthermore, the profession plays a key role in addressing global inequity and injustice. Enabling engineers to address complex technological challenges like climate change requires the development of new skills such as evaluating justice dimensions of engineering and collaborating with diverse communities [1].…”
Section: Literature Reviewmentioning
confidence: 99%